Thermal Gradient Changes Caused by Water in the Soil - Duque, M. R. (2013)
The heat flow density data published in the Geothermal Atlas of Europe (1992) show relatively high values for temperature gradients measured in holes in the SW area (Portugal and Spain) of the Iberian Peninsula. This study tries to explain this fact based in the presence of water at relatively high temperatures outside the holes where the measurements were made, and the inclination of strata, derived from samples taken from the boreholes. We used a two-dimensional numerical model based on the finite volume method. Equations governing the transfer of energy by conduction and advection and fluid flow, were solved. Thermal conductivity values of the rocks and water may vary spatially as well as the porosity. Thermal conductivity values were measured but values of the hydraulic conductivity and porosity are unknown. Due to this fact, the models are tested with different values of these parameters. The heat flow density value considered for the region is 60 mWm-2 and the thermal gradient is calculated using the value of thermal conductivity. The results obtained with the models are compared with those published. Different solutions can be obtained for a given hole.